PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN MENGGUNAKAN MODEL DIRECTED READING THINKING ACTIVITY (DRTA) DIKELAS 1V SDN 22 MATA AIR BARAT KOTA PADANG - Yulianis; Sry Apfani (Jurnal Riset Pendidikan Dasar Dan Karakter, 2025)
The problem in this study stems from the low reading comprehension skills of students in grade IV SDN 22 Mata Air Barat Padang City. It can be seen that many students are still lazy to read, students can get bored and bored in reading, the teacher has not implemented the stages of reading, namely, Pre-reading, Post-reading, and WhileReading. This study discusses how students' reading comprehension skills use the Directed Reading Thinking Activity (DRTA) model in class IV SDN 22 West Air Springs, Padang City. This study aims to improve students' reading comprehension skills using the Directed Reading Thinking Activity (DRTA) model in class IV SDN 22 West Springs of Padang City. The approach used in this research is a qualitative approach and a quantitative approach. The place of this research is in the fourth grade of SDN 22 Mata Air Barat Padang City with a total of 25 students. Based on the research results, it can be seen that the DRTA model in each cycle shows good results. in pre-reading cycle 1, it obtained a percentage of 67.6% with sufficient criteria and increased in cycle II with a percentage of 83.40% with very good criteria. When reading cycle 1, it obtained a percentage of 65% with sufficient criteria and increased in cycle II with a percentage of 86% with very good criteria. The post-reading cycle obtained a percentage of 72.6% with sufficient criteria and increased in the second cycle with a percentage of 89.76% with very good criteria.